Strong association between malnutrition, inflammation, and depression in elderly patients. A new novel geriatric complex based on malnutrition; MID complex? Malnutrition, Inflammation and Depression in Elderly Patients - Turkbeyler, İbrahim Halil; Öztürk, Zeynel Abidin; Gol, Mehmet; Efendioglu, Eyüp Murat; Sahinbeyoglu, Seyma (Progress in Nutrition, 2020)
Background/Aim: The proportion of elderly individuals is increasing worldwide and geriatric syndromes(GS) are associated with a decreased life span. Malnutrition and depression are highly prevalent among the elderlyand associated with poor clinical prognosis. This study investigated the frequency of inflammation and depressivesymptom comorbidity in the context of a cause-and-effect relationship among elderly patients with malnutritionand/or malnutrition risk. Material and Methods: Participants in this cross-sectional study included 217 individualsaged 65 years and over. Comprehensive geriatric assessment was performed to participants. Malnutrition anddepression were diagnosed according to the Mini-Nutritional Assessment (MNA-SF) Tool and Yesavage GeriatricDepression Scale (YGDS), respectively. Inflammation status were diagnosed according to the C-reactive protein(CRP) levels. Results: According to MNA-SF, 41 (18.9%) patients were malnourished, 82 (37.8%) at a risk ofmalnutrition, and 94 (43.3%) possessed normal nutrition. Among the malnourished patients, 51.2% experiencedCRP elevation and 70.7% displayed symptoms of depression. Patients at risk of malnutrition experienced 39.0%CRP elevation, and 46.3% displayed depression symptoms. There was a statistically significant negative correlationbetween MNA-SF scores and YGDS and CRP (r: -0,201, p: 0,003, r: -0,495, p: 0,000, respectively). The incidenceof inflammation-depression association in malnourished patients was 36.6%, 12.2% in those at risk for malnutrition,and 10.6% in those with normal nutrition. Conclusion: Physicians should be informed regarding the associationamong malnutrition, inflammation, and depression in geriatric patients.